An imperfect production model for breakable multi-item with dynamic demand and learning effect on rework over random planning horizon - Amalesh Kumar Manna; Leopoldo Eduardo Cárdenas-Barrón; Barun Das; Ali Akbar Shaikh; Armando Céspedes-Mota; Gerardo Trevi\~no-Garza (Journal of Risk and Financial Management, 2021)
In recent times, in the literature of inventory management there exists a notorious interest in production-inventory models focused on imperfect production processes with a deterministic time horizon. Nevertheless, it is well-known that there is a high influence and impact caused by the learning effect on the production-inventory models in the random planning horizon. This research work formulates a mathematical model for a re-workable multi-item production-inventory system, in which the demand of the items depends on the accessible stock and selling revenue. The production-inventory model allows shortages and these are partial backlogged over a random planning horizon. Also, the learning effect on the rework policy, inflation, and the time value of money are considered. The main aim is to determine the optimum production rates that minimize the expected total cost of the multi-item production-inventory system. A numerical example is solved and a detailed sensitivity analysis is conducted in order to study the production-inventory model.
Keywords: 330; breakable items; reworked; shortages; partial backlogging; learning effect; random planning horizon